Safety quality of coconut juice sold in Miagao, Iloilo. - Clavel, Rochelle Anne Madali
Coconut juice collected from the three selected sources, A, B, and C in Miagao, Iloilo were subjected to microbiological analyses which include Total Plate Count (TPC), Yeast and Molds Count (YMC), and detection of Eschericia coli, Staphylococcus aureus and Salmonella. The coconut juice was also subjected to physico-chemical analyses (pH, TSS, TA, and cyclamate). Based on the microbiological criteria for coconut juice in the Philippines, coconut juice from the three sources exceeded the TPC (1x104 cfu/ml) and the yeast and molds count (250 cfu/ml) for coconut juice except for YMC of source A during the third period of sampling. One-way ANOVA (α = 0.05) showed no significant differences in the TPC, and yeast and molds count of the coconut juice from the three sources. The Most Probable Number of fecal coliform of the coconut juice which ranged from 8.33 - 11.000 MPN/ml also exceeded the microbiological criteria for coconut juice in the Philippines, which is <1 MPN/ml. One-way ANOVA (α = 0.05) revealed the following: pH of the coconut juice ranging from 6.58 - 6.77 had no significant difference among the sources. TSS of the coconut juice from the sources, which ranged from 1.71 - 3.53° Brix also, had no significant difference. TA of the coconut juice ranging from 0.07-0.78% had no significant difference as well. Pearson correlation revealed that the correlation between Titratable Acidity and Yeast and Molds Count was significant at 0.01 level (2-tailed). It also revealed the correlation between Total Soluble Solids and most probable number of E. coli was significant at 0.05 (2-tailed). E. coli was present in coconut juices from the three selected sources except in B during the third period of sampling and C during the second period sampling. All coconut juice from the three selected sources tested negative for the presence of Salmonella in all sampling periods. However, S. aureus were present in coconut juice from all sources. Cyclamate was detected in the coconut juice from the three sources. The high TPC, yeast and molds count, presence of E. coli, and S. aureus indicated that the coconut juices from sources A,B, and C were not safe for consumption.